Insight into the chemical composition, antioxidant capacity, meat quality, fatty acid profile, and volatile compounds of yellow-feathered chickens fed with fermented pineapple residue - Panpan Lu; Ruiting Guo; Chunlian Zou; Hang Chen; Dan Chen; Lu Yang; Huize Tan; Siqiao Wu; Yaxue Lv; Zhengzhong Xiao; Chunqi Gao (Food Chemistry: X)
This study aimed to evaluated the effect of dietary fermented pineapple residue (FPR) on the chemical composition, antioxidant capacity, meat quality, fatty acid profile, and volatile compounds in yellow-feathered chickens. GC-IMS technique combined with multivariate analysis were performed to clarify the key volatile compounds. The results showed that dietary FPR improved meat quality by increasing the antioxidant capacity and pH value and decreasing cooking loss of breast muscle. The fatty acid profile was altered in breast muscle of chickens that fed with FPR. GC-IMS detected 43 volatile compounds in breast muscle, including mainly aldehydes, alcohols, esters, and ketones. Among them, 12 volatile compounds could serve as potential aroma markers to distinguish meat flavor of chickens fed with FPR. Correlation analysis revealed that C18:1n9c, C18:2n6, and PUFA are important contributors for meat flavor formation. In conclusion, dietary FPR improved antioxidant capacity, meat quality, fatty acid profile, and volatile compounds of breast muscle in chickens.